Unpacking the separation of powers - Baroš, Jiří (Edward Elgar Publishing, 2020)
The concept of separation of powers can be used as a slogan, as an idea, or as a concept. On the conceptual level, it may be endowed with many different, even incompatible, meanings. To understand the contemporary challenges to separation of powers, both old and new, we thus need a more scrupulous theoretical and conceptual understanding of the principle. Accordingly, this chapter first embeds separation of powers in the broader context of modern constitutionalism and distinguishes its limiting and enabling rationales. Second, it unpacks separation of powers into four constitutive components: separation of institutions, separation of functions, personal incompatibility, and checks and balances. Third, it shows how important it is to distinguish these components when analysing the recent populist attacks on separation of powers both in Central Europe and beyond and stresses the significance of the temporal dimension of populist rule. Finally, it calls for greater scholarly attention to the limiting rationale of separation of powers, to the impact of the rise of unelected actors, and to the interconnectedness between separation of powers and the problem of political representation.